Finding Exemplars of Research on Academic Programs - Toombs, William ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1982)
Exemplars of research on academic programs are considered in relation to the qualities of research and types of information used as a framework for analysis. It is suggested that serious investigations of the postsecondary curriculum are characterized by: efforts to move from particularistic approaches to the stipulation of universalistic variables; a use of empirical research to initiate and clarify the rudimentary concepts now in use; and recognition that the reality of the situation has more complexity than most research designs can incorporate so that it is not desirable or necessary to seek practical results all the time. Research on the college curriculum has some parallels with field study in the social sciences. Principal methodological considerations suggested by Zelditch (1962) are: (1) histories and incidents (chronicles, interpretations, and synthesis incidents--cases and persons); (2) distributions and frequencies (normative and descriptive studies of effects, outcomes, and impacts); and (3) generally known rules and statuses (focusing on curriculum or critical processes). Historical analyses that carry the process of interrelating society and the curriculum to the point of synthesis are few. The study of incidents, which includes individual cases, ideas, and situations, has grown enormously since 1960, often under impetus from the Carnegie Commission. Building a quantitative framework within which curricula features can be placed and compared is important. The value of comprehensive data sets is increasing as uncertainty rises and more variability among students, institutions, and programs appears. Crane's formulation that a coherent field of study requires a cognitive structure and a system of social interaction and assessment is advocated. (SW)
ERIC Note: Paper presented at the American Educational Research Association (New York, NY, March 19-23, 1982).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Education; Case Studies; College Curriculum; Data Bases; Educational Assessment; Educational Research; Postsecondary Education; Research Methodology; Research Projects; Surveys; Trend Analysis; Speeches/Meeting Papers; Information Analyses